A policentrikus városhálózat-fejlesztés gondolatisága országos területfejlesztés dokumentumokban : az ír és magyar példa - Besze, Tamás (Közép-Európai Közlemények, 2009)
The regionalism as a new phenomena became increasingly an important part of the European Economic Community development policy from the1960s. As a result of these process the ESDP (European Spatial Development Perspective) and the ESPON (European Spatial Planning Observation Network) which can be named the base documents of the European spatial policy, emphasize the importance of the policentric city development concept from the aspect of the territorial competitiveness. The goal of the survey is to demonstrate point of the well-balanced spatial planning by the Irish and Hungarian spatial development documents and methods.